If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12+6k=24
We move all terms to the left:
-12+6k-(24)=0
We add all the numbers together, and all the variables
6k-36=0
We move all terms containing k to the left, all other terms to the right
6k=36
k=36/6
k=6
| .11d+10=6d | | 8t-(-4)=68 | | (3x+1)=(x+1) | | 2p-7=11-p | | x=8+x=5 | | 6x-14+3=40 | | 5z+8+4z+10=180 | | 7x-9=2x-36 | | 67x+x-15=180 | | 16x-1=14x+13 | | 6(x+6)+5=5(-x+6) | | 7x-9°=2x-36° | | 14=6+8(x-13) | | X+14+x+10=20 | | -4x+3.5=9-2x | | 11q-6=3q-8q | | (7x-9)°=(2x-36)° | | 1+5p=2(p-4) | | 24-6y=5y-9 | | 5.9–x=-4.5–5x | | 3(7+2a)+5(1+a)=-7a+5a | | -11.75-9.6j-2.88=-3.7j+18.41 | | 2.3y+2+3.1y=4.3y+1.6+1 | | 7x-47=5x+23 | | 11a-24=31 | | 43k=86 | | 5y=5+4(3y-3) | | b+45+2b-90=180 | | 4(-2x-10)=-48 | | 6-4(3x+1)=14 | | 12t=74t=6 | | 24-6y=5y-9* |